Determinasi Adopsi Financial Technology Syariah oleh Mahasiswa Generasi Z : Peran Digital Financial Literacy, Sharia Trust, dan Perceived Risk - Reja Fadillah, Alan; Hamzani, Umiaty; M. Helmi, Syarif (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of digital financial literacy, sharia trust, and perceived risk on the adoption of Islamic financial technology (fintech) among Generation Z students. This research employed a quantitative approach using a survey method through online questionnaires distributed via Google Forms. The sampling technique used purposive sampling with a total of 228 Generation Z student respondents who had experience using digital financial services. The data were analyzed using SPSS through validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, F-test, T-test, and coefficient of determination analysis. The results showed that digital financial literacy, sharia trust, and perceived risk simultaneously had a significant effect on the adoption of Islamic fintech. Partially, digital financial literacy and sharia trust had a positive and significant effect on Islamic fintech adoption, while perceived risk also significantly influenced Islamic fintech adoption. The coefficient of determination indicated that the independent variables explained 54.5% of the variation in Islamic fintech adoption, while the remaining percentage was influenced by other variables outside this study. This study indicates that digital financial literacy, trust in sharia principles, and risk perception are important factors influencing the adoption of Islamic fintech among Generation Z students. Keywords : Digital Financial Literacy, Sharia Trust, Perceived Risk, Islamic Fintech Adoption, Generation Z